El sistema terrateniente y los límites de la política monetaria española liberal en la primera mitad del siglo XIX - Prieto Tejeiro, Enrique (2011)
This paper aims to deepen the understanding of the transition from traditional to modern monetary systems and its impact on economic growth in the Spanish economy over the first half of the nineteenth century. The main sources on which the study of this period’s monetary policy is based, are, among others, the proceedings of the parliamentary committee; during the Trienio Liberal, these related to a draft for the complete reform of the monetary system inherited from the Antiguo régimen, whose results would be constrained by three factors: firstly, by the persistence of traditional institutions; secondly, by difficulties in linking this monetary reform with the discussions that were taking place in the more developed countries, particularly in England; and, thirdly, the short duration of the period in which it took place, and the restoration of the old monetary policy with the Tarifa de Tolosa in 1823.